Flood detection system with GSM / Azim Aimanuddin Mat Akhir, Amirul Asraf Roslan and Arif Zakwan Ab Ghani - Mat Akhir, Azim Aimanuddin; Roslan, Amirul Asraf; Ab Ghani, Arif Zakwan (2015)
Flood is one of the natural disasters that cause many destruction and losses to the victim. The consequences of flood are the losses of life and belongings, spreading of diseases, destruction of building and crops and so on. This disaster will affect the people and the country severely which is why we need to build a project that can detect the incoming flood so that the damage can be reduced. This project is built for home use which will alert the owner if the device is sensing a water rise in the house. In this way, it will allow the owner to take precautions step and time to save their precious things and their family before the water rise to a dangerous level. Furthermore, this device consist of a water sensor circuit, buzzer and GSM that connect PIC 16F783A. It will trigger the buzzer and the GSM will send a message when the sensor is detecting flood. The main purpose of this project is to prevent the loss of life, reduce the damage of household property and to give an appropriate time for the owner to take precaution step and evacuate.